An Update of Pitted Keratolysis: A Review - Hoque, Tania; Uddin, Bhuiya Mohammad Mahatab (Journal of Current and Advance Medical Research, 2018)
Pitted keratolysis is a bacterial infection of the soles of the feet or less commonly, the palms of the hands. Pitted keratolysis is easily identified by its shallow, crater-like pits. Collection of specimen using swab may be helpful to identify causative bacteria and skin scraping is often taken to exclude fungal infection. The diagnosis is sometimes made by skin biopsy revealing characteristic histopathological feature of Pitted Keratolysis. Treatment generally consists of hygienic measures, sometimes supplemented by medication and perhaps on oral medication. This review is aimed to consolidate present information about aetiopathogenesis, diagnosis and management of Pitted Keratolysis. It is worth mentioning that Pitted Keratolysis is non-contagious. Journal of Current and Advance Medical Research 2017;4(1):27-30